2014
DOI: 10.1186/s12888-014-0370-0
|View full text |Cite
|
Sign up to set email alerts
|

Differentiating ADHD from oral language difficulties in children: role of movements and effects of stimulant medication

Abstract: BackgroundThe current study was designed to test if an objective measure of both attention and movement would differentiate children with Oral Language Disorders (OLD) from those with comorbid Attention Deficit/Hyperactivity Disorder (ADHD) and if stimulant medication improved performance when both disorders were present.MethodsThe sample consisted of thirty-three children with an identified oral language disorder (of which 22 had comorbid ADHD) ages 6 to 13 who were enrolled in a yearlong intensive learning i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 32 publications
1
2
0
1
Order By: Relevance
“…As for the objective movement difference estimated in the group of subjects with ADHD with and without medication intake, the results show that there are statistically significant differences for the 17 joints analysed, being in all of them the average of movement higher in the group without taking medication. The results we have obtained are similar to those of previous studies that indicate that medicated ADHD children show significantly less motor activity than non-medicated ADHD children [ 41 , 42 , 43 ].…”
Section: Discussionsupporting
confidence: 91%
“…As for the objective movement difference estimated in the group of subjects with ADHD with and without medication intake, the results show that there are statistically significant differences for the 17 joints analysed, being in all of them the average of movement higher in the group without taking medication. The results we have obtained are similar to those of previous studies that indicate that medicated ADHD children show significantly less motor activity than non-medicated ADHD children [ 41 , 42 , 43 ].…”
Section: Discussionsupporting
confidence: 91%
“…The fact is that language difficulties occur in greater proportion in children with ADHD than in the general population and are not restricted to the difficulties related to communication skills (11) . Although there is considerable evidence that language difficulties are associated with ADHD, they have not been sufficiently explored in the national scenario (12,13) or even international (14) . Given the above, this study aimed to compare the receptive vocabulary and verbal comprehension of schoolchildren with and without ADHD, and to compare their performance with the normative values of the tests applied.…”
Section: Introductionmentioning
confidence: 99%
“…The results of research on the frequency of these comorbid diseases are different. Recent study estimated 50% of children with ADHD have a comorbid language deficit, while 20 to 60% of children with ADHD have one or more learning disabilities or language problems [23]. Study from 2016 identified language impairments in the majority within the ADHD and reading disorder in >40% in children with ADHD [24].…”
Section: Comorbidity With Specific Developmental Speech and Language mentioning
confidence: 99%